2013
DOI: 10.5433/1679-0359.2013v34n1p7
|View full text |Cite
|
Sign up to set email alerts
|

Análise dialélica na avaliação do potencial de híbridos de milho para a geração de populações-base para obtenção de linhagens

Abstract: ResumoDoze híbridos comerciais de milho foram intercruzados, conforme um dialelo completo. Esses genótipos e três testemunhas foram avaliados em látice triplo na região Centro-Sul do Paraná, nos municípios de Laranjeiras do Sul, Guarapuava e Cantagalo. Os dados referentes à produção de espigas despalhadas, altura de planta e altura de espiga foram submetidos à análise dialélica conjunta, segundo o método 4 de Griffing, em que foram avaliados apenas os F 1 . Foi verificado efeito significativo da capacidade ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
34
0
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 6 publications
7
34
0
10
Order By: Relevance
“…Studying the combining abilities of the twelve commercial hybrids in a complete diallel conducted in three locations, Oliboni et al (2013) found analogous significances to those detected in this study with regard to the 'treatments x environments' interactions for yield, average plant height and average ear height. Amorim and Souza (2005) discuss that commercial simple hybrids still present in the market associate essential characteristics for good agricultural performance, reuniting a high number of already fixed favorable loci with elevated production.…”
Section: Pfann Et Al (2009) Verified For Grain Yield Thatsupporting
confidence: 50%
See 1 more Smart Citation
“…Studying the combining abilities of the twelve commercial hybrids in a complete diallel conducted in three locations, Oliboni et al (2013) found analogous significances to those detected in this study with regard to the 'treatments x environments' interactions for yield, average plant height and average ear height. Amorim and Souza (2005) discuss that commercial simple hybrids still present in the market associate essential characteristics for good agricultural performance, reuniting a high number of already fixed favorable loci with elevated production.…”
Section: Pfann Et Al (2009) Verified For Grain Yield Thatsupporting
confidence: 50%
“…Various authors report the predominance of additive effects and partial dominance in the genetic control of plant height and ear height (SAWAZAKI et al, 2000;OLIBONI, 2013). The predominance of the additive effects in the control of grain yield has also stated been by various authors (SANTOS et al, 1985;PINTO et al, 2001;SCAPIM et al, 2002, LOCATELLI et al, 2002CARVALHO et al, 2004).…”
Section: Pfann Et Al (2009) Verified For Grain Yield Thatmentioning
confidence: 88%
“…Breeding programs whose objective is to obtain superior hybrids chose to use germplasm with a narrow genetic base for the formation of their base population [Hallauer, Carena and Miranda Filho (2010), Oliboni et al (2013), Souza Neto et al (2015 and Senhorinho et al (2015)]; studies report that commercial single cross hybrids have been used by breeders of outcrossed plants for the formation of segregating populations and is due to the advanced breeding process that these genotypes already utilize. Similarly, this can be an important strategy to generate base populations of autogamous plants such as tomato.…”
Section: Introductionmentioning
confidence: 99%
“…O efeito significativo da CEC para a produtividade de grãos, com valores de elevada magnitude, tanto positivos quanto negativos (Tabela 3), evidencia a possibilidade de selecionar genitores que podem gerar boas populações para o melhoramento interpopulacional, para extração de linhagens, que ao serem cruzadas, poderão gerar híbridos com elevada heterose (OLIBONI et al, 2013). A ausência de efeito significativo da interação ´CEC x densidades` (Tabela 1), indica que o comportamento da CEC dos cruzamentos se manteve constante, independentemente da densidade.…”
Section: Resultsunclassified
“…Para balizar o processo de seleção de genitores com maior potencial no melhoramento genético e para o entendimento dos efeitos genéticos que estão evolvidos na manifestação dos caracteres é comum o emprego de cruzamentos dialélicos (CHAVES et al, 2008;BALDISSERA et al, 2012;OLIBONI et al, 2013), que podem também fornecer estimativas de parâmetros importantes para seleção de genitores em diferentes condições de manejo.…”
Section: Introductionunclassified